MicroRNA-19 contributes to the malignant phenotypes of osteosarcoma in vitro by targeting Pax6 - Qingbing Meng; Ming Dai; Xuejun Nie; Wensheng Zhang; Xingli Xu; Jian Li; Hongxin Mu; Xiaolan Liu; Ling Qin; Xiaoqi Zhu; Jun Yan; Minqian Zheng (Tumor Biology)
This study was conducted to detect the expression of miR-19 and Pax6 (Paired box protein 6) in human osteosarcoma cells and the effects on biological characteristics of osteosarcoma cells. Quantitative real-time polymerase chain reaction was used to detect the expression of Pax6 and miR-19 in normal human osteoblasts (hFOB 1.19) and osteosarcoma cell lines (U2OS, Saos-2, and MG-63). Results showed that miR-19 was significantly upregulated in osteosarcoma cell lines compared with that in hFOB 1.19 cells, while the expression of Pax6 messenger RNA was significantly downregulated. Pax6 was defined as the target gene of miR-19 which was validated by luciferase reporter gene analysis. Results indicated that miR-19 had an interaction with Pax6 3′-untranslated region. At the same time, the protein expression of Pax6 was significantly decreased in the MG-63 cells transfected with miR-19 mimic and was notably enhanced in osteosarcoma MG-63 cells transfected with miR-19 inhibitor. These data suggested that Pax6 was a target of miR-19 in osteosarcoma MG-63 cells. The effects of miR-19 on the biological behavior of MG-63 cells were determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide, flow cytometry, and Transwell assay. Results showed that the downregulation of miR-19 inhibited cell viability, reduced the percentage of cells in S phase and the number of cells passing through the Transwell chamber, and increased the number of apoptotic cells. Western blot analysis showed that the inhibition of miR-19 significantly increased the expression of epithelial proteins (E-cadherin and β-catenin) and decreased the expression of mesenchymal protein (Vimentin), extracellular signal–regulated kinase, and phosphorylated extracellular signal–regulated kinase in MG-63 cells. MiR-19 inhibitor and Pax6 small interfering RNA were simultaneously transfected into MG-63 cells. Results from 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide, flow cytometry, and Transwell assay demonstrated that the inhibition of Pax6 expression in MG-63 cells could reverse the cell biological effects induced by the inhibition of miR-19 expression. Based on these findings, it was suggested that miR-19, upregulated in osteosarcoma cells, negatively regulated the expression of Pax6, which can promote the malignant phenotypes of osteosarcoma cells via activation of the extracellular signal–regulated kinase signaling pathways. Therefore, miR-19/Pax6 may offer potential for use as a target for the treatment of osteosarcoma.